Life over Limb: Lower Extremity Ischemia in the Setting of Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA). Issue 6 (June 2018) - Wasicek, Philip J.; Teeter, William A.; Yang, Shiming; Hu, Peter; Hoehn, Melanie R.; Stein, Deborah M.; Scalea, Thomas M.; Brenner, Megan L.
Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a temporizing maneuver used to decrease hemorrhage, and thus perfusion, below the level of aortic occlusion (AO). We sought to investigate lower extremity ischemia in patients who received REBOA. Between February 2013 and September 2016 patients at a tertiary center that received REBOA and survived more than six hours were enrolled. Thirty-one patients were identified, the mean ISS was 40 ± 14 and inhospital mortality was 39 per cent. Twenty received REBOA in zone 1 (distal thoracic aorta). Three (15%) developed lower extremity compartment syndrome (LECS) after zone 1 REBOA. Injury of iliofemoral arteries and veins was each associated with calf fasciotomies (both P = 0.005). A longer duration of AO at zone 1 was associated with calf and thigh fasciotomy (P = 0.046 and P = 0.048, respectively). Iliofemoral arterial injury was associated with thigh fasciotomy (P = 0.04). Eleven patients received REBOA in zone 3 (distal abdominal aorta). Five (45%) patients underwent fasciotomy; four (36%) due to LECS. Femoral arterial injury was associated with calf fasciotomies (P = 0.02). There was no association with sheath size or laterality and need for fas-ciotomy. Neither groin access for REBOA or AO solely caused limb loss or LECS. The contribution to distal ischemia by REBOA remains unclear in patients with lower extremity injury.